Safety and efficacy of durvalumab in patients with head and neck squamous cell carcinoma: results from a phase I/II expansion cohort. (March 2019) - Segal, Neil H.; Ou, Sai-Hong I.; Balmanoukian, Ani; Fury, Matthew G.; Massarelli, Erminia; Brahmer, Julie R.; Weiss, Jared; Schöffski, Patrick; Antonia, Scott J.; Massard, Christophe; Zandberg, Dan P.; Khleif, Samir N.; et al.
Abstract: Introduction: Durvalumab selectively blocks programmed cell death ligand-1 (PD-L1) binding to programmed cell death-1. Encouraging clinical activity and manageable safety were reported in urothelial carcinoma, non–small-cell lung cancer (NSCLC), hepatocellular carcinoma (HC) and small-cell lung cancer (SCLC) in a multicenter phase I/II study. Safety and clinical activity in recurrent/metastatic head and neck squamous cell carcinoma (HNSCC) were evaluated in the expansion phase. Methods: Patients received 10 mg/kg of durvalumab intravenously every 2 weeks for 12 months or until confirmed progressive disease or unacceptable toxicity. The primary objective was safety; clinical activity was a secondary objective. Results: Sixty-two patients were enrolled and evaluable (received first dose ≥24 weeks before data cutoff). Median age was 57 years; 40.3% were human papillomavirus (HPV)-positive; 32.3% had tumour cell PD-L1 expression ≥25%, and 62.9% were current/former smokers. They had a median of 2 prior systemic treatments (range, 1–13). All-causality adverse events (AEs) occurred in 98.4%; drug-related AEs occurred in 59.7% and were grade III–IV in 9.7%. There were no drug-related discontinuations or deaths. Objective response rate (blinded independent central review) was 6.5% (15.0% for PD-L1 ≥25%, 2.6% for <25%). Median time to response was 2.7 months (range, 1.2–5.5); median duration was 12.4 months (range, 3.5–20.5+). Median progression-free survival was 1.4 months; median overall survival (OS) was 8.4 months. OS rate was 62% at 6 months and 38% at 12 months (42% for PD-L1 ≥25%, 36% for <25%). Conclusions: Durvalumab safety in HNSCC was manageable and consistent with other cohorts of the study. Early, durable responses in these heavily pretreated patients warrant further investigation; phase III monotherapy and combination therapy studies are ongoing. Clinical trial registry: clinicaltrials.gov NCT01693562; MedImmune study 1108. Highlights: Durvalumab monotherapy was safe in previously treated recurrent/metastatic head and neck squamous cell carcinoma. Durable antitumour responses were observed, similar to other tumour cohorts. Objective response rate and disease control rate were greater in patients with ≥25% vs <25% tumoural PD-L1 expression.